Technology Platforms as Drivers of Innovation in the Digital Economy in Indonesia’s MSMEs - Ahmad Taufiqurrahman Asy’ari; Agus Hermawan (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
Digital transformation has become a major force in driving innovation in the Micro, Small and Medium Enterprises (MSMEs) sector in Indonesia. This research examines the role of technology platforms as a key driver in facing challenges and capitalizing on opportunities in the digital economy era. Through a descriptive qualitative approach, this study analyzes how MSMEs adopt digital platforms such as e-commerce, digital payments, and cloud-based technology to improve operational efficiency, expand market reach, and drive sustainable business growth. The results show that the utilization of technology platforms not only accelerates innovation in products and services, but also increases the competitiveness of MSMEs in the global market. However, technology adoption still faces obstacles such as limited digital literacy, infrastructure, and access to financing. Therefore, support from various parties, including the government, private sector, and educational institutions, is needed to create an inclusive and sustainable digital ecosystem for MSMEs in Indonesia.